AN ANALYSIS OF STUDENTS’ SPEAKING GRAMMATICAL ERRORS AT THE SECOND GRADE SMA N 10 JAMBI ACADEMIC YEAR 2017/2018 - Rasari Triani Putri; Sri Marmoah; Erisa Kurniati (JELT: Journal of English Language Teaching, 2018)
The purpose of the Research is to find the grammatical errors made by the students in speaking at the second grade SMA N 10 JAMBI Academic year 2017/2018. The method used in this study is qualitative. The subject I studied was second grade students of SMA N 10 Jambi. The students are 20 people. The research is taken in SMA N 10 Jambi .The researcher gives one topic to the students about daily activity and ask them to talk what their daily activity with a duration of 1-3 minutes. The minimum response indicates that there 10 students who used simple present tense. The result shows that grammar error of all pupils is 27,5%. The students make the most mistakes in the Misformation Errors that is the error in grammar or words. In order to improve the students’ ability speaking, the students have to do more practice especially about the grammar. My advice to the reader if you have an interest in writing / researching in order to further explore the research.Key Words: Grammatical Errors, Simple Present tense